PENGARUH ALAT PERMAINAN EDUKATIF (APE) DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA DI SD NEGERI SE- KECAMATAN SIRAH PULAU PADANG - Rensi Apriyanti; Syarwani Ahmad; Pahlawan Pahlawan (Jurnal Manajemen Pendidikan, 2026)
This investigation is grounded in the need for creative and engaging instructional media to enhance learning quality at the primary school level. A quantitative method with a descriptive–correlational design was employed. The research population consisted of all teachers working in public elementary schools within the district, and the sample was selected using a cluster random sampling technique centered on Cluster 6. This cluster includes six schools with a total of 69 participating teachers. Data were collected through a questionnaire using a five-point Likert scale, designed to assess three variables: educational play tools (X₁), teachers’ learning motivation (X₂), and students’ learning outcomes (Y). Each variable comprised 30 items. The data were analyzed using Pearson Product–Moment correlation and multiple regression, processed with SPSS version 26. The findings indicate that (1) educational play tools contribute positively and significantly to students’ learning outcomes (r = 0.564; sig. 0.000 < 0.05, suggesting a moderate-to-strong correlation), (2) teachers’ learning motivation shows a positive but statistically insignificant relationship with students’ learning outcomes (r = 0.208; sig. 0.086 > 0.05, indicating a weak and non-significant effect), and (3) both variables jointly exert a positive and significant influence on students’ learning outcomes (R = 0.601; sig. 0.000 < 0.05, reflecting a strong combined effect).